Prospective, Randomized, Double-Blind Evaluation of the Efficacy of a Single-Dose Hyaluronic Acid for the Treatment of Patellofemoral Chondromalacia. Issue 6 (24th June 2019) - Hart, Joe M.; Kuenze, Chris; Norte, Grant; Bodkin, Stephan; Patrie, James; Denny, Claire; Hart, Jennifer; Diduch, David R.
Background: Patellofemoral pain is common in the young and active populations. Nonoperative management is limited and focuses on physical therapy. Hyaluronic acid (HA) is an injectable device that has been used for the treatment of knee osteoarthritis. Hypothesis: A single injection of HA would reduce pain and improve function in patients with patellofemoral pain who had previously failed conservative management. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: A total of 86 patients with patellofemoral pain (65 females, 21 males; mean ± SD age, 27.0 ± 7.7 years; height, 168.6 ± 8.9 cm; weight, 74.6 ± 17.0 kg; body mass index, 26.2 ± 5.2 kg/m 2 ) enrolled in this study after failing conservative management. Patients were randomly allocated to either 6 mL of HA or a sham injection. All patients were prescribed an additional home exercise program, including lower extremity strengthening and flexibility exercises, and were evaluated at 1, 3, and 6 months. Outcome assessments included patellofemoral pain assessment with a visual analog scale during a single-legged squat, KOOS (Knee injury and Osteoarthritis Outcome Score), Kujala score, Tegner activity rating, and normalized isometric knee extension strength. Group assignment was revealed after the 6-month assessment, and crossover treatment was offered to patients in the sham group who were still symptomatic. Linear mixed models were used to compare outcomes between groups and across time. Results: A total of 45 patients were randomized to HA injection and 41 to sham, with 6 patients lost to follow-up (93% follow-up rate). Patients in both groups experienced a significant reduction in visual analog pain ratings and significant improvements in all domains of the KOOS and in Kujala scores at 6 months when compared with baseline measurement ( P < .05); however, there was no significant difference between groups. There were no differences observed over time or between groups for normalized knee extension strength or Tegner activity rating ( P > .05). Conclusion: HA injection had no clinically meaningful effect on pain or functional outcomes in patients diagnosed with patellofemoral pain. Improvements were observed for both groups in patient-reported pain and function, with no change in quadriceps strength or activity rating. Registration: NCT01771952 (ClinicalTrials.gov identifier).